Implementasi Terapi Menggambar Pada Anak Penyandang Tunarungu Menggunakan Komunikasi Bisindo: Implementasi Terapi Menggambar Pada Anak Penyandang Tunarungu Menggunakan Komunikasi Bisindo - asa, priscila; Langingi, Ake Royke Calvin; Melany Kumayas; Greita Marya Selina Timpal; Sri Rejeki Monica Suparlan; Zefania Pagayang (Journal of Excellence Humanities and Religiosity, 2025)
Deaf children experience partial or complete loss of hearing function, which has complex impacts on their lives. The purpose of this activity is to implement drawing therapy for hearing-impaired children using sign language communication. The method used is the implementation method of drawing or coloring. Drawing therapy is very important to apply to hearing-impaired children to alleviate boredom and even anxiety. The results obtained from this activity indicate a change in feelings to become happier and a more cheerful mood with art therapy. Other therapies are also needed, besides drawing therapy, such as learning basic mathematics to stimulate brain intelligence.